Medication Use Among Patients Reporting Xerostomia of an Academic Dental Clinic. (October 2022) - Krajewski, Michael P.; Mo, QingXiang; Lu, Chi-Hua; Cantos, Albert; Feuerstein, Steve; Brandt, Michael J.; Wahler, Robert G.
Background: Global prevalence of xerostomia has been reported at 22% (range 0.01%-45%), negatively impacting oral health, nutrition intake, and quality of life. The causal relationship between xerostomia and medications remains uncertain but greater understanding could guide interventions. Objective: To describe the demographic characteristics and medication regimens in patients with xerostomia of an academic dental clinic. Method: This is a retrospective academic dental clinic record review from July 1, 2018 to October 27, 2020. Patient records were obtained from the University at Buffalo, School of Dental Medicine. Xerostomia status was determined via query of electronic health records and validated by manual review. Pharmacologic class and xerostomic potential of medications were identified by the Veterans Affairs Drug Classification System and drug compendia, respectively. Predictors of medication use were assessed using a multiple logistic regression model. Results: Of 37 403 examined records, 366 (0.98%) were identified as xerostomic. After excluding confounding factors (Sjogren's and radiation), 275 of 317 patients received at least one xerostomic medication, majority were female (240, 66%) versus male (126, 34%). Mean ± (SD) age was 64.9 ± 15.11 years. A total of 208 (57%) patients were aged ≥65. The median number of total and xerostomic medications were 8 (interquartile range [IQR], 4-12) and 4 (IQR, 2-7), respectively. The 3 most prevalent xerostomic pharmacologic classes were antidepressants (131, 35%), gastric medications (101, 28%), and vitamin D (87, 24%). Conclusion: Despite observed prevalence of xerostomia lower than global prevalence, xerostomic medication burden for patients experiencing xerostomia was high. Pharmacist-led interprofessional collaborations should be investigated to reduce xerostomic burden.